2020
DOI: 10.1371/journal.ppat.1008426
|View full text |Cite
|
Sign up to set email alerts
|

Killer cell proteases can target viral immediate-early proteins to control human cytomegalovirus infection in a noncytotoxic manner

Abstract: Human cytomegalovirus (HCMV) is the most frequent viral cause of congenital defects and can trigger devastating disease in immune-suppressed patients. Cytotoxic lymphocytes (CD8 + T cells and NK cells) control HCMV infection by releasing interferon-γ and five granzymes (GrA, GrB, GrH, GrK, GrM), which are believed to kill infected host cells through cleavage of intracellular death substrates. However, it has recently been demonstrated that the in vivo killing capacity of cytotoxic T cells is limited and multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…We also investigated the ability of the UL141 mAbs to promote the control of virus using a recently developed 10-day viral dissemination assay (VDA), which captures the effects of both cytotoxic and noncytotoxic virus control in a fully autologous system ( Figure 7, D and E , and refs. 54 , 55 ). The UL141 mAbs demonstrated a striking ability to enhance NK-mediated virus control in this assay, confirming that they can act as powerful effectors for long-term control of virus infection, even at low effector/target (E/T) ratios.…”
Section: Resultsmentioning
confidence: 99%
“…We also investigated the ability of the UL141 mAbs to promote the control of virus using a recently developed 10-day viral dissemination assay (VDA), which captures the effects of both cytotoxic and noncytotoxic virus control in a fully autologous system ( Figure 7, D and E , and refs. 54 , 55 ). The UL141 mAbs demonstrated a striking ability to enhance NK-mediated virus control in this assay, confirming that they can act as powerful effectors for long-term control of virus infection, even at low effector/target (E/T) ratios.…”
Section: Resultsmentioning
confidence: 99%
“…It is interesting to note that anti-HCMV activity of monocyte derived macrophages has been observed and that this was not mediated by IFNγ nor primary IFNα or IFNβ although the identity of the secreted factor responsible for the activity was not determined (Becker et al, 2018 ). Other studies have shown that even in the presence of IFNγ or IFNα or IFNβ neutralizing antibodies, HCMV infection can still be controlled by lymphocytes in a non-cytotoxic manner, with granzymes implicated in control (Shan et al, 2020 ). A non-biased mass spectrometry-based approach is likely to be required to elucidate the key antiviral components of effective secretomes.…”
Section: Discussionmentioning
confidence: 99%
“…45 Gerada et al identified that GZMB cleaved multiple herpes simplex virus (HSV) type 1 and varicella-zoster virus (VZV) gene products (HSV-infected cell protein (ICP) 4, HSV ICP27, VZV open reading frame (ORF) 62 and VZV ORF4), which demonstrate important roles in viral replication. 46 Furthermore, GZMB induces the cleavage of viral immediate-early (IE) proteins IE1 and IE2 in human cytomegalovirus (HCMV)infected cells, 47 which are vital for triggering a temporally coordinated cascade of transcriptional events that lead to expression of early and late viral proteins essential for HCMV reactivation and production of infectious virus. 48,49 When Jurkat cells infected with the vaccinia virus were subjected to treatment with GZMB, a halt in viral protein synthesis and a decrease in the production of infectious new virions occurred because GZMB induced the cleavage of eukaryotic initiation factor 4 gamma 3.…”
Section: Gzmb and Elimination Of Viruses Or Virus-infected Cellsmentioning
confidence: 99%
“…Additionally, GZMB that enters the cells mainly plays a significant role in eliminating tumour cells/virus-infected cells, [27][28][29][37][38][39][40]44 eliminating intracellular bacteria and parasites, 19,20,41,42 and viruses. [46][47][48][49][50] However, extracellular GZMB plays an important role in inducing the occurrence and development of diseases (such as inflammation, 8,84,[93][94][95][96][97][98][99] fibrosis, 88,115 CAV, 83 AAA, 89 autoimmune blistering diseases, 92,93,108 age-related macular degeneration, 16 SLE/LN, 109 RA, 4 SSPE, 110 cardiovascular disease, [112][113][114] and wound healing [117][118][119][120] ).…”
Section: Nanomaterials Delivery Systems For Gzmbmentioning
confidence: 99%